The Impact of Deteriorating Library Facility Quality on Student Reading Engagement and Literacy at SMAS PGRI Arga Makmur Indonesia - Wandira, Joy Aji; Riady, Yasir; Arisanty, Melisa; Prasakti, Angga Warda (IJLTP, 2025)
SMAS PGRI Arga Makmur is the oldest private institution for Senior High School education in Arga Makmur. The study titled The Effect of Declining Quality of Library Facilities on the Reading Activities of SMAS PGRI Arga Makmur Students seeks to investigate the extent of the decline in library facilities to date and to determine whether this deterioration adversely affects students' reading activities. The study employs a quantitative methodology. The data collection included four teachers and four pupils who were fully aware of the condition of the school library facilities. The data is derived from primary sources obtained directly through surveys, interviews, and observations. This study aimed to assess the available school facilities, categorizing them as seriously damaged. The study's results indicated that most respondents rated the library room facilities as 2 out of 5, signifying low condition.